Epistaxis: comparison of chemical cautery with topical vasoconstrictor in adult anterior epistaxis - Hussain, Raj Tajamul; Deeba, Farah; Ali, Mariya; Ahmad, Rauf (International Journal of Research in Medical Sciences, 2020)
Background: To compare efficacy of 75% silver nitrate chemical cautery as opposed to topical vasoconstrictor spray (xylometazoline 0.1%) in adult anterior epistaxis. Methods: This randomized controlled trial study was carried out at SMHS Hospital Srinagar from Jan 2019 to Dec 2019. 110 subjects that presented to ENT & HNS emergency with epistaxis and fulfilled the inclusion criteria were selected. Subjects were randomly distributed into two groups. Group-A individuals were treated by cauterization with 75% silver nitrate and Group-B individuals were treated with topical vasoconstrictor spray (xylometazoline 0.1%). All the subjects were reviewed at 1 month and success was determined in terms of control of epistaxis from same side of nose. Results: The mean age of the cohort was 48.5yrs (age range, 17-59). There were total 60 (54.4%) males and 50 (45.4%) females among the cases. Both the groups were comparable as regards the age, sex, duration and frequency of epistaxis. 91.2% cases in Group-A (silver nitrate cautery) and 73.5% cases in Group-B (xylometazoline spray 0.1%) had no further epistaxis at one-month follow-up (p=0.014). Conclusions: Chemical cauterization with silver nitrate is a feasible and safe technique for the treatment of adult anterior epistaxis and is more effective than topical vasoconstrictor spray.